On a spectral problem in magnetohydrodynamics and its relevance for the geodynamo. Issue 3 (15th October 2018) - Stefani, Frank; Tretter, Christiane
Abstract : One of the most remarkable features of the geodynamo is the irregular occurrence of magnetic field reversals. Starting with the operator theoretical treatment of a non‐selfadjoint dynamo operator, we elaborate a dynamical picture of those reversals which relies on the existence of exceptional spectral points.